Re-orient :global economy in the Asian Age - Frank, Andre Gunder (Vistaar Publications,1998., 1998)
"Frank explains the Rise of the West from 1400 forward in world economic and demographic terms, with a sweeping historical perspective that places it in clear conjunction with the Decline of the East around 1800." "Anyone interested in Asia, in world systems and world economic and social history, in international relations, and in comparative area studies will have to take into account Frank's exciting reassessment of our global economic past and future."--BOOK JACKET.